2011
DOI: 10.1007/s11249-011-9785-7
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Property of Ni3Al Matrix Composites with Addition of BaMoO4

Abstract: The Ni 3 Al matrix composites with addition of 10, 15, and 20 wt% BaMoO 4 were fabricated by powder metallurgy technique, and the tribological behaviors were studied from room temperature to 800°C. It was found that BaAl 2 O 4 formed during the fabrication process. The Ni 3 Al composites showed poor tribological property below 400°C, with high friction coefficients (above 0.6) and wear rates (above 10 -4 mm 3 /Nm). However, the composites exhibited excellent self-lubricating and anti-wear properties at higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…It is well known that the tribological properties of materials are closely related to the tribofilm on the worn surface generated during sliding (Huang,et al (15); Zhu, et al (26)). Huang, et al (15) reported that the covering percentage of the tribofilm could be changed with sliding speed and load.…”
Section: Compositions Of the Tribofilm On The Worn Surfacesmentioning
confidence: 99%
“…It is well known that the tribological properties of materials are closely related to the tribofilm on the worn surface generated during sliding (Huang,et al (15); Zhu, et al (26)). Huang, et al (15) reported that the covering percentage of the tribofilm could be changed with sliding speed and load.…”
Section: Compositions Of the Tribofilm On The Worn Surfacesmentioning
confidence: 99%
“…[23][24][25][26][27] Zhu et al 23 was found to have an excellent lubricating property and its CoF is about 0.15 at 500 • C. The friction and wear characteristics of ZrO 2 (Y 2 O 3 )-BaCrO 4 coating at elevated temperatures have been studied by Ouyang et al 27 They found that ZrO 2 (Y 2 O 3 )-BaCrO 4 coating exhibits a distinct improvement in wear resistance and frictional characteristics as contrasted to the ZrO 2 (Y 2 O 3 ) coating at elevated temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a series of Ni3Al high temperature self-lubricating composites were developed in Lanzhou Institute of Chemical Physics, Chinese Academy of Sciences [15,[48][49][50][51][52][53][54][55]. The selflubricating composites, which consist of Ni3Al matrix with Cr/Mo/W, Ag and BaF2/CaF2 additions, exhibit the low friction coefficient and wear rate at a wide temperature range from room temperature to 1000 °C.…”
Section: Ni3al Matrix High Temperature Self-lubricating Compositesmentioning
confidence: 99%
“…In a search for even higher temperature solid lubricants for Ni3Al, many efforts have been performed on inorganic salts and fluorides of alkali metals [51][52][53].…”
Section: Effect Of Solid Lubricant On the Tribological Behaviormentioning
confidence: 99%